AIAA Modeling and Simulation Technologies Conference 2010
DOI: 10.2514/6.2010-7915
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Feedback Components of the Neuromuscular System in a Pitch Control Task

Abstract: This goal of this study is to understand which parts of the the neuromuscular system contribute during a pitch control task. A novel method developed at the Delft University of Technology allows us to determine the contribution of the neuromuscular feedback system by identifying the admittance, which is the frequency response function of the yielded displacement due to an external force perturbation which applied to control inceptor.In an experiment in a full-motion flight simulator, the neuromuscular admittan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…This is important, as it might suggest that these parameters are related. Regarding the physical system that is modeled, i.e., a set of connected limbs, such a relationship would agree with expectations, as changing admittance is known to involve many muscles across the under-arm, upper-arm, and torso [27].…”
Section: B Bdft Modelmentioning
confidence: 93%
“…This is important, as it might suggest that these parameters are related. Regarding the physical system that is modeled, i.e., a set of connected limbs, such a relationship would agree with expectations, as changing admittance is known to involve many muscles across the under-arm, upper-arm, and torso [27].…”
Section: B Bdft Modelmentioning
confidence: 93%
“…Research has focused on neuromuscular adaptation during disturbancerejection tasks that require humans to adopt different neuromuscular settings in response to force disturbances on the control device [23][24][25]. More recent work has shown that the neuromuscular response in an aircraft tracking task with different dynamics of the control device is highly variable [26,27]. Other studies indicated that the ankle-foot neuromuscular response of car drivers changes when a haptic aid is employed during a car-following task [21].…”
Section: Introductionmentioning
confidence: 97%
“…The pilot neuromuscular and visual responses are estimated by using three different multiloop identification techniques. The first is based on cross-spectral density analysis (CSD-based method) and has been commonly used for identifying pilot responses [21,27]. However, a recent work showed that the CSD-based method might provide a biased estimate of neuromuscular response if a noninterference hypothesis is not fulfilled [28].…”
Section: Introductionmentioning
confidence: 99%
“…This measurement is regularly performed for standard task conditions, such as the Force-Task (FT), in which the human operator is instructed to keep the force on the manipulator constant, the position task (PT), in which the instruction is to keep the manipulator in a set position and relax task (RT), in which the operator should suppress responses to manipulator movement. Using the data from the test signal, measured force on the manipulator and measured manipulator displacement, and possibly aided by EMG measurement, the NMS admittance properties can be identified in several possible approaches Damveld et al (2010) and Venrooij et al (2014). An example of the results of such a measurement is given in Figure 1.…”
Section: Introductionmentioning
confidence: 99%
“…The choice of a test signal is often based on experience, and often a test signal found in literature or used before is re-used, without inspecting its influence on the subject's (Damveld et al, 2010) behavior. In this paper, design choices for the identification signal are evaluated by simulation of a PT and a FT experiment, and evaluation of the endpoint variance (manipulator position for the PT and manipulator moment for the FT) for consistent variation of the model parameters.…”
Section: Introductionmentioning
confidence: 99%